2008
DOI: 10.1016/j.exer.2008.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Postreceptoral contributions to the light-adapted ERG of mice lacking b-waves

Abstract: The purpose of this study was to determine the contributions of postreceptoral neurons to the lightadapted ERG of the Nob mouse, a model for complete-type congenital stationary night blindness (CSNB1) that lacks a b-wave from depolarizing bipolar cells. Ganzfeld ERGs were recorded from anesthetized adult control mice, control mice injected intravitreally with L-2-amino-4-phosphonobutyric acid (Control APB mice) to remove On pathway activity, and Nob mice. ERGs also were recorded after PDA (cis-2, 3-piperidine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 49 publications
4
54
0
Order By: Relevance
“…This allowed the contributions from both cone photoreceptors and OFF-bipolar cells to be examined. 39 Inspection of DMD waveforms (bold traces) superimposed on those of WT (thin traces) showed that the scotopic OPs, scotopic b-wave, and, minimally, the photopic b-wave may exhibit reduced amplitudes. Particularly in the scotopic signals, larger a-wave components were revealed with the reduction of the b-waves.…”
Section: Scotopic Threshold Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…This allowed the contributions from both cone photoreceptors and OFF-bipolar cells to be examined. 39 Inspection of DMD waveforms (bold traces) superimposed on those of WT (thin traces) showed that the scotopic OPs, scotopic b-wave, and, minimally, the photopic b-wave may exhibit reduced amplitudes. Particularly in the scotopic signals, larger a-wave components were revealed with the reduction of the b-waves.…”
Section: Scotopic Threshold Responsesmentioning
confidence: 99%
“…39 Following this component is the P ON (probably homologue to the b-wave), which reflects the ON-response. As in the measurements with the mesopic sawtooth stimuli, we confirm previous observations that stimulus offsets do not elicit a d-wave in the mouse.…”
Section: Asymmetrical Retinal On/off Dysfunction Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was neither designed to separate the ON-and OFF-components of the ERG nor the OFF-contribution to the OP response. Future studies are needed for such analysis which will require, for example, longlasting stimulus light, pharmacological dissections to identify the ON-and OFF-components of the OPs (Kojima & Zrenner 1978;Wachtmeister 1981bWachtmeister , 1998Shirato et al 2008;Raghuram et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, comparisons of a-wave measurements in wild-type and nob mice can lead to the inaccurate conclusion that the a-wave is changed. Although the awave is often measured from baseline to the trough of the wave (106), it is more directly monitored by measuring it from baseline to the amplitude at a fixed time such as 15ms after the flash if the experimental models exhibit an ablated b-wave (107). The second, positive-going corneal b-wave corresponds to ON bipolar cell depolarization, or opening of the TRPM1 cation channels allowing cation influx into the cell.…”
Section: Using Crispr/cas9 To Generate Genetically Modified Mouse Modelsmentioning
confidence: 99%